Construcción de un sistema inteligente para la asignación dinámica de turnos en el área de consulta externa del Hospital Regional Isidro Ayora, mediante el análisis heurístico utilizando hardware y software libre. - Becerra González, Carmen Elizabeth (2014)
The present titling project called ARDAC includes the analysis, design and implementation of an intelligent system of allocation of shifts in the Area of consultation outside of the Hospital Regional Isidro Ayora, which allows to centralize and improve the management and distribution of shift process, manage the schedules of each physician care, present generated shift reports and present the code of the turn on a display which was built using free hardware. In the case of the treating physicians system allows to monitor the shifts that have been assigned and record a patient's attention. Therefore, that for the development process that begins with the analysis phase and interpretation of the system information gathering techniques were used and appropriate scientific methods that were applied to all the actors involved in the development of our project, also used ICONIX as a methodology of software development, which allowed an agile development simplified, iterative and incremental without deviating from the needs of the user. This system was implemented in the C programming language which is a free software, used the WxWidget library for the development of graphical interfaces and MySql was used as the database manager. Also for the theoretical support described in the literature review section was collected information with respect to concepts about the system and the development tools used were defined. In addition to the theoretical support described in the literature review section was collected information with respect to concepts about the system and the development tools used were defined. The results section details the process for the development of ARDAC following the methodology of development, thus describes the requirements of the system, design of the application; diagrams as classes, use cases among others to achieve the expected results; as well as the testing and analysis of results. The discussion shows how each of the objectives established at the beginning of the project were achieved. Finally the conclusions are exhibited obtained after finishing the project, as well as there are included the recommendations derived based on the experience reached during the whole process of development of the present project named ARDAC.